Penggunaan Model Cooperative Learning Tipe Numbered Head Together Untuk Meningkatkan Minat Dan Hasil Belajar IPS Kelas IV SDN 17 Palaluar - Yulinova, Misda (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study is to describe the increase in students interest in problem solving through the NHT model in social studies learning, to describe increasing students’ interest in making summaries through the NHT model in social studies learning in class, to describe increasing students’ interest in doing exercises through the NHT model in social studies learning and Indentifying increased student learning outcomes in explaining learning materials through the NHT model in social studies learning at SDN 17 Palaluar Koto VII District. This research isa quantitative research with correlational method. Sampling was done using cluster random sampling technique. The result showed that there was a positive relationship between interest and social studies learning outocomes for fourth grade students. The data showed that : the ability of students to solve problems from 60% to 85% making summaries increased from 62,59% to 77,50%, doing exercises increased from 72,50% to 92,50% and the ability to explain the subject matter increased from 65% to 85%. Based on the analysis and discussion of the research result, it can be concluded that social studies learning using the Numbered Head Together type Cooperative Learning model for fourth grade students at SDN 17 Palaluar can increase interest and social studies learning outcomes.